SEMANTIC, SYNTACTIC AND PRAGMATIC FEATURES OF ENGLISH QUOTATIONS IN LINGUISTICS THESES - Triệu Thị Sâm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis examines semantic, syntactic and pragmatic features of English Quotations (EQs) in Linguistic Theses (LTs). The data for analysis in this thesis are 617 samples of EQs collected from the linguistic theses and journal articles. The study was conducted based on the combination of variety methods such as descriptive, analytic and inductive one. The study focuses on analysing linguistic features of EQs in LTs in terms of semantic categories, syntactic structures and pragmatic functions in the light of semantic, syntactic, pragmatic theories; quotation theory and locutionary, illocutionary, cognitive act theories. With regard to semantic features, lower-level linguistic (phatic act and rhetic act), illocutionary act and cognitive act were discovered in pure, direct, indirect and mixed quotation. In analysing syntactic features, the research shows that pure quotation has only lower level linguistic structure (rhetic structure and phatic structure) in the different plane with the structure of the entire sentence;whereas, direct, indirect, mixed quotations in LSs are simultaneous with LF-structures (entire sentence) and lower-level linguistic structures. Finally, the findings in pragmatic functions in EQs in LTs shows that there are 7 main pragmatic categories commonly employed with the highest frequency of Narrative and Grammatical purpose. On the basis of the findings, some practical implications for citing references in linguistic studies and scientific studies are suggested. It is expected that the findings of this paper will be useful for those who are interested in EQs and academic writing.